Shanidar Cave. A Palaeolithic Site in Northern Iraq and its Relationship to the Stone Age Sequence of Iraq - Solecki, R. S.
Introduction — Physiography of Iraq — Pleistocene History — History of the Palaeolithic Archaeology — Shanidar Cave — Stratigraphy.